FEEDING DWARF ELEPHANTGRASS SILAGE ON THE HEALTH OF BOERKA GOATS REARED IN SANDA VILLAGE BALI - M. F., BAKARA; DOLOKSARIBU, L.; DUARSA, M. A. P. (Majalah Ilmiah Peternakan, 2024)
This study conducted from June–August 2021 was to determine the effect of feeding 0, 250, and 750 g/head/ day of dwarf elephantgrass silage on health of boerka goats reared in Sanda Village, Bali. Twelve boerka goats used in this study were fed with forage 10% of individual body weight. A completely randomized design with three fe- eding treatment, i.e., forage only (P0), forage+250 g/head/day of dwarf elephantgrass silage (P1), forage+750 g/ head/day of dwarf elephantgrass silage (P2) with four replications were used in this study. The observed variables: FAMACHA© score, endo-parasite, erythrocyte, and leukocyte levels of goat’s blood. The results showed that all bo- erka goats were in good health conditions showing by their FAMACHA© scores were less than two. Five of 12 goats were found Ostertagia sp., and Haemonchus sp., in their gastro-intestinal which was mild infection (280 epg). The highest level of erythrocyte 2.82±0.26 (1012/L) occurred on P0 and P2 treatments, followed by 2.55±0.26 (1012/L) on P1 treatment. The highest level of leukocyte 14.59±1.76 (109/L) occurred on P1 treatment, followed by 13.03±1.76 (109/L) on P2 treatment, and 9.09±1.76 (109/L) on the P0 treatment. In summary, boerka goats in Sanda Village, Bali that consumed 750 g/head/day tended to have better health status.